PEMANFAATAN QR CODE PADA PURA BATURGANGSIAN SEBAGAI MEDIA PENDIDIKAN AGAMA HINDU DI DESA TINGGARSARI KECAMATAN BUSUNGBIU KABUPATEN BULELENG - Komang Agus Triadi Kiswara; I Made Yudabakti; I Wayan Sudiarsa; I Putu Yoga Pratama Putra; Ida Ayu Anggriani (JURNAL SEWAKA BHAKTI, 2023)
The important role of technology in human life is of course very large, technology can be used in all fields, one of which is in educational media. The use of technology in educational media is a progressive step in an effort to keep up with the times. In accordance with the jargon that is often raised, the function of technology is to lighten what is heavy, bring what is far away. Likewise, the use of technology in education, the presence of technology is to help students more easily access learning materials. One of the technological media that can be utilized in the educational process is the QR Code media. QR Code itself stands for Quick Response Code, which is a two-dimensional barcode introduced by the Japanese company Denso Wave in 1994. One of the problems currently being faced by the Tinggarsari Village Community is the lack of public knowledge about the Bebaturan temple in the village. Bebaturan temple itself is a very ancient temple and has differences from the temples that are currently developing, so that the information data is still very minimal and is only known by a handful of people. So that the scattered data needs to be collected and presented in writing. The final data is then presented in the form of a QR Code so that people can easily access it. The problem solving method used is the data triangulation method.